1989
DOI: 10.1172/jci114285
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion molecules of cultured hematopoietic malignancies. A calcium-dependent lectin is the principle mediator of binding to the high endothelial venule of lymph nodes.

Abstract: This study documents that a calcium-dependent phosphomannosyl-binding site on human lymphoid malignancies mediates attachment to the peripheral node high endothelial venule (PNHEV). The phorbol ester PMA coordinately upregulates lectin activity and binding to the PNHEV in the human T-lymphoblastic cell line Jurkat but not in the less phenotypically mature lines HSB2, Molt4, CEM, and HPB-ALL. In contrast, expression of CD18, CD2, and several common epitopes of the putative adhesion receptor gp90fIerme (CD44) di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

1990
1990
1993
1993

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…Consistent with data on cross-species recognition of pln HEV by human and murine lymphocytes (44,46) human cells express a closely related homologue of the murine pin HR that probably functions in an analogous manner (4,38,49). Furthermore, at least two other adhesion molecules, the endothelial leukocyte adhesion molecule (ELAM-1) (2) and the platelet membrane granule protein, GMP 140/PADGEM (3,23,31), show the same arrangement of protein motifs as gp90 MEL and its human homologue, suggesting that this family of lectin egf complement-cell adhesion molecules or LEC-CAMs (42), may be widespread in the vascular system.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with data on cross-species recognition of pln HEV by human and murine lymphocytes (44,46) human cells express a closely related homologue of the murine pin HR that probably functions in an analogous manner (4,38,49). Furthermore, at least two other adhesion molecules, the endothelial leukocyte adhesion molecule (ELAM-1) (2) and the platelet membrane granule protein, GMP 140/PADGEM (3,23,31), show the same arrangement of protein motifs as gp90 MEL and its human homologue, suggesting that this family of lectin egf complement-cell adhesion molecules or LEC-CAMs (42), may be widespread in the vascular system.…”
supporting
confidence: 89%
“…Previous studies demonstrated that gp90 MEL, either as a cell surface-associated molecule (44,46,54) or as an isolated molecule (17), is able to bind to the M6P-rich polysaccharide, PPME. In both cases, MEL-14 mAb inhibits the interaction as does EGTA, a chelator of calcium ions.…”
Section: Analysis Of Mhr-igg Chimera For Ppme Bindingmentioning
confidence: 99%
“…) Binding of cell lines was carried out as described for lymphocytes . The human Jurkat JS-978 (Stoolman and Ebling, 1989) and mouse 3ßC13 (Gallatin et al ., 1983) cell lines bind well to PLN HEV in frozen sections. The mouse cell line Ll-2 does not bind either PLN or mucosal HEV; and mouse lines TKl and TKI43 avidly bind mucosal HEV, but do not bind well to PLN HEV (Butcher et al ., 1980 ;Gallatin et al ., 1983) .…”
Section: Binding Oflymphocytes and Cell Lines To Pnadmentioning
confidence: 99%
“…Additionally, the yeast-derived, M6P-rich phosphomannan monester core from Hansenula hostii known as PPME, and the sulfated, fucose-rich polysaccharide called fucoidin (from brown seaweed) were shown to be potent inhibitors of lymphocyte binding to PN HEV while having little effect on the binding of lymphocytes to PP HEV (Stoolman and Rosen, 1983;Yednock et al, 1987b, Yednock, T. A., M. S. Singer, Y. Imai, and S. D. Rosen, manuscript in preparation). With PPME-derivatized microbeads as a probe for cell surface receptors, it was demonstrated that the carbohydrate dependency of lymphocyte binding to PN HEV can be accounted for by a calcium-dependent, lectin-like receptor on the lymphocyte surface (Yednock et al, 1987b;Stoolman et al, 1987;Stoolman and Ebling, 1989). Moreover, experiments demonstrating MEL-14 mAb inhibition of PPME bead binding to lymphocytes and the coexpression of PPME bead binding with the MEL-14 epitope on lymphoma variants argued that the receptor, detected by PPME beads, was closely related and probably identical to gp90 uEL (Yednock et al, 1987a).…”
mentioning
confidence: 99%